2017
DOI: 10.1002/brb3.685
|View full text |Cite
|
Sign up to set email alerts
|

Parental brain‐derived neurotrophic factor genotype, child prosociality, and their interaction as predictors of parents’ warmth

Abstract: BackgroundParental warmth has been associated with various child behaviors, from effortful control to callous‐unemotional traits. Factors that have been shown to affect parental warmth include heritability and child behavior. However, there is limited knowledge about which specific genes are involved, how they interact with child behavior, how they affect differential parenting, and how they affect fathers. We examined what affects paternal and maternal warmth by focusing on the child's prosocial behavior and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 61 publications
1
12
1
Order By: Relevance
“…We also tested whether child and parent gender moderated the strength of (evocative) rGE. Although the previous literature on gender effects is somewhat inconclusive (Avinun & Knafo, ; Avinun & Knafo‐Noam, ), this study did not find any significant interaction between G2 gender and G2 genes in explaining the variance in parenting.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…We also tested whether child and parent gender moderated the strength of (evocative) rGE. Although the previous literature on gender effects is somewhat inconclusive (Avinun & Knafo, ; Avinun & Knafo‐Noam, ), this study did not find any significant interaction between G2 gender and G2 genes in explaining the variance in parenting.…”
Section: Discussioncontrasting
confidence: 80%
“…If this is the case, then it is likely that evocative rGE rather than passive rGE account for the responses children experience in terms of parenting. It is further possible that the strength of the (evocative) rGE is moderated by the parent or child gender (Avinun & Knafo, ; Avinun & Knafo‐Noam, ). Because boys and girls might receive different parenting and because mothers and fathers might express differential parenting qualities, we test the interactions between G2 gender and G2′s genome‐wide genotype variation in explaining emotional warmth and intolerance.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, there is evidence that child behavior is more likely to affect harsh parenting in fathers (Hajal et al, 2015). Furthermore, as mentioned, we have previously found that the BDNF gene moderates the warmth of fathers and not of mothers, in response to children's prosocial behavior (Avinun & Knafo-Noam, 2017). Sex differences have been observed in various BDNF related phenotypes (e.g., Advani, Koek, & Hensler, 2009;Lommatzsch et al, 2005;Monteggia et al, 2007;Shalev et al, 2009), which may be partly explained by the interaction between BDNF and estrogen (reviewed in Wu, Hill, Gogos, & Van Den Buuse, 2013).…”
Section: Sex As a Moderator Of Genetic Effectssupporting
confidence: 53%
“…It is involved in neuronal survival and growth during development and in the adult brain (Notaras, Hill, & van den Buuse, 2015), thus making the BDNF gene a potential candidate for gene-environment interaction (GxE) and behavioral plasticity studies. Recently, we have shown (Avinun & Knafo-Noam, 2017) that fathers, but not mothers, who are carriers of the Met allele of the BDNF gene, are more likely to change their level of warmth in accordance with their child's prosocial behavior, than carriers of the Val/Val genotype. Recently, we have shown (Avinun & Knafo-Noam, 2017) that fathers, but not mothers, who are carriers of the Met allele of the BDNF gene, are more likely to change their level of warmth in accordance with their child's prosocial behavior, than carriers of the Val/Val genotype.…”
Section: The Brain-derived Neurotrophic Factor (Bdnf) Genementioning
confidence: 99%
See 1 more Smart Citation